2010
DOI: 10.4028/www.scientific.net/kem.443.456
|View full text |Cite
|
Sign up to set email alerts
|

Edge Chipping of Rock: An Experimental Study

Abstract: This paper investigates experimentally the edge chipping of a rock to assess the cutting performance of a conical and a pyramidal tip. It was found that the conical tip generates many radiated cracks and results in a larger amount of fine rock grains due to crashing. The size of chips produced by the pyramidal tip is bigger. It was concluded that the critical chipping energy has approximately a linear relation with h9/4 of which h is the depth of cut of the tip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Bao [5] and Yao [62] postulated that if the loading direction in edge chipping is regarded as the direction of cutting in rock cutting and the side face in edge chipping tests is treated as the cutting surface, the edge chipping is similar to the linear rock cutting tests in mining to some extent and might be used to estimate the peak cutting force as shown in Figure 2.7.…”
Section: Bao Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Bao [5] and Yao [62] postulated that if the loading direction in edge chipping is regarded as the direction of cutting in rock cutting and the side face in edge chipping tests is treated as the cutting surface, the edge chipping is similar to the linear rock cutting tests in mining to some extent and might be used to estimate the peak cutting force as shown in Figure 2.7.…”
Section: Bao Modelmentioning
confidence: 99%
“…Yao [62] made an experimental investigation in which a conical tipped pick has been compared with a pyramidal tipped pick in laboratory edge chipping tests. It was found that the generated rock chips have the similar shape and the chipping energy is proportional to the 9/4 th power of the depth of cut.…”
Section: Bao Modelmentioning
confidence: 99%